The impact of COVID-19 pandemic on nosocomial multidrug-resistant bacterial bloodstream infections and antibiotic consumption in a tertiary care hospital - Metan, Gökhan; Demir Çuha, Mervenur; Hazirolan, Gülsen; Telli Dizman, Gülçin; Tanriverdi, Elif Seren; Otlu, Baris; Tas, Zahit; Zarakolu, Pinar; Arik, Zafer; Topeli, Arzu; Akinci, Seda Banu; Ünal, Serhat; et al. (German Medical Science GMS Publishing House, 2022)
We investigated the change in the epidemiology of nosocomial bloodstream infections (BSIs) caused by multidrug-resistant bacteria during Coronavirus Disease (COVID-19) and antibiotic consumption rates at a pandemic hospital and at the Oncology Hospital which operated as COVID-19-free on the same university campus. Significant increases in the infection density rate (IDRs) of BSIs caused by carbapenem-resistant (CRAB) and ampicillin-resistant (ARE) were detected at the pandemic hospital, whereas carbapenem-resistant BSIs were increased at the non-pandemic Oncology Hospital. Pulsed field gel electrophoresis showed a polyclonal outbreak of CRAB in COVID-19 intensive care units. Antibiotic consumption rates were increased for almost all antibiotics, and was most significant for meropenem at both of the hospitals. Increased IDRs of CRAB and ARE BSIs as well as an increased consumption rate of broad-spectrum antibiotics emphasize the importance of a multimodal infection prevention strategy combined with an active antibiotic stewardship program.